2007
DOI: 10.1371/journal.pone.0000629
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde at Low Concentration Induces Protein Tau into Globular Amyloid-Like Aggregates In Vitro and In Vivo

Abstract: Recent studies have shown that neurodegeneration is closely related to misfolding and aggregation of neuronal tau. Our previous results show that neuronal tau aggregates in formaldehyde solution and that aggregated tau induces apoptosis of SH-SY5Y and hippocampal cells. In the present study, based on atomic force microscopy (AFM) observation, we have found that formaldehyde at low concentrations induces tau polymerization whilst acetaldehyde does not. Neuronal tau misfolds and aggregates into globular-like pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 58 publications
2
45
0
2
Order By: Relevance
“…Fixatives such as formaldehyde cross-link proteins and nucleic acids (Gustavson, 1956;Nie et al, 2007) and cause cell shrinkage. Different dyes have different quantum yields (Cosa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Fixatives such as formaldehyde cross-link proteins and nucleic acids (Gustavson, 1956;Nie et al, 2007) and cause cell shrinkage. Different dyes have different quantum yields (Cosa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde derived from local metastasized tumor tissues excites peripheral nociceptive neurons and thus can induce cancer pain [7] . More surprisingly, we and others found that formaldehyde at low pathological concentrations induces misfolding and aggregation of neuronal tau protein, leading to apoptosis of hippocampal neurons in vitro [8] , and even cognitive impairment in human beings and loss of memory functions in animals [9,10] .…”
Section: Introductionmentioning
confidence: 60%
“…Tissue-derived endogenous formaldehyde even at such a low concentration can induce pain behavior [7,22] . Previous studies have demonstrated that formaldehyde exposure at 0.01-0.1% (~3.3 to ~33 mmol/L) induces mis-folding and aggregation of tau protein in hippocampal neurons [9] , which is essential to beta-amyloidinduced neurodegeneration [23] . Cognitive impairments in senile dementia have also been associated with elevated endogenous formaldehyde concentration [10] .…”
Section: Discussionmentioning
confidence: 99%
“…A formaldehyde molecule first interacts with a Tau monomer. As additional FA molecules interact with other Tau monomers, the FA molecules polymerise, finally resulting in the cross-linking of the Tau molecules (Nie et al, 2007).…”
Section: In Vitro Investigations 21 Low Concentrations Of Formaldehymentioning
confidence: 99%